Tracing the evolution of key traits in dorid nudibranchs - Silvia Prieto-Baños; Kara K. S. Layton (PLoS ONE, 2025)
Reconstructing trait evolution is critically important for elucidating the processes generating biodiversity. However, this work is in its infancy in non-model clades for which we lack a basic understanding of their ecology and biology. Here, we compile information about prey preference, chemical acquisition and colour pattern in dorid nudibranchs (Nudibranchia: Doridoidei) and reconstruct their ancestral states using a multi-gene phylogeny to investigate the evolution of these key traits. Our analyses show that the most recent common ancestor (MRCA) of Doridoidei preferred sponge prey from which they sequestered metabolites, and subsequent shifts to different prey types and de novo synthesis of defensive compounds occurred multiple times independently across the phylogeny. Additionally, the MRCA likely exhibited complex colour patterns, including spots or stripes, with uniform morphotypes evolving in most families. Despite the fact that many dorid nudibranchs derive both metabolites and pigments from their prey, we found no evidence of correlated evolution amongst these traits. As part of this work, we present a multi-gene phylogeny for Doridoidei with representatives from 88 genera and 18 families, but there remain issues with poor support across the tree. Nonetheless, for the first time, we explore the evolution of key traits that contributed to the diversification of dorid nudibranchs, highlighting the need for more refined trait data and greater phylogenetic resolution for future work.